Smart city tra competitività urbana e vocazione turistica il governo della dimensione turistica delle città - La Rocca, Rosa Anna (Smart City, Urban Planning for a Sustainable Future, 2023)
The interest in urban tourism has been topical in the field of socio-geographical studies since 1980. However, already early studies tended to separate scholars involved in tourism and those in urban planning. This division is not logic given that the World Tourism Organization in the Economic Review of World Tourism reported in the 1970s the growing demand for tourist destinations in cities. Nonetheless, a real contribution from scientific research to the issues arisen by tourism on the cities' organization has been achieved yet. The study does not aim to fill this gap but does encourage the analysis of tourism as an integrated phenomenon in the process of governing urban and territorial transformations It is no longer an external force but a part of the everyday urban activity. . The separation between "the place of work" (city) and the "place of leisure" (outside the city) has characterized the approaches of tourism research for the last thirty years. Based on this theoretical framework, this monograph illustrates the recent evolutions of tourism in its relationship with cities, confronting the challenges faced by cities, revisiting the Smart City paradigm applied to the tourist destination. It also presents an insightful perspective on the lights and shadows of urban tourism.